(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2017)
This article discusses the role of the institution of mufti in Malaysia in ensuring the sanctity of Muslims’ belief and the rightfulness of their deeds in this challenging era of globalization. This role is closely related to the function of mufti in issuing fatwa or decrees. In Malaysia, only the Sunnah wa al-Jama’ah school is acceptable by law. It is on this premise that contrary teachings are determined by way of fatwa as deviant and thus prohibited. Proper attributes of the successors of the prophets are identified, and suggestions are provided so that the institution of the mufti will be more effective Keywords: mufti, akidah (Islamic belief), deeds, Malaysia, globalization